Analytical elements of good governance from the perspective of international institutions and the constitution of the Islamic Republic of Iran - hamid shakeri (مطالعات تطبیقی حقوق کشورهای اسلامی)
Although there are some serious controversies about governance quality, it is one of the most fundamental needs of human community that its necessity is not deniable. Nevertheless, original concern of all theorists is exercise of justice and prevention of despotism and dictatorship in every country’s Constitution, besides defining basic principles, structure, hierarchy, position and limits of state political authority, it determines dictatorship citizens rights and regulates power relations. Undoutedly, good governance is the most fundamental principle in defining and drawing basic rights. Good governance is a new discourse which is defined by factors such as rule of law, participation, responsibility, accountability, transparency, efficiency and effectiveness. In recent years, good governance has been paid attention so much. Good governance factors imply for which its exercise is needed to implement based on a national model. Research findings represent that each of good governance factors have been emphasized in Iranian Constitution a lot. To implement these factors, we have dealt with intensity of these indicators after Iran Revolution.This study is trying to clarify good governance concept and factors and also take such factor into consideration in the Iranian Constitution. At the end, to promote good governance in Iran, some recommendations have been expressed. The research method is the content analysis method and the data and information have been collected through library and document studies.